Spatio-temporal Variation of Landuse Carbon Budget and Carbon Compensation Zoning in Beibu Gulf Urban Agglomeration Area - Wang Zhengqiang; Qin Menglin; Tang Shibin; Zhao Yincheng; Pang Yayue; Gong Yuanhong (Shuitu baochi tongbao)
[Objective] The evolution characteristics and coupling coordination relationship between the spatial scale of cities, and the spatiotemporal pattern of the carbon budget in urban agglomeration areas were analyzed, and a regional evaluation system for carbon compensation was constructed in order to provide a reference for implementing strategies at the urban agglomeration level to achieve the goal of carbon neutrality. [Methods] Based on an analysis of the spatial and temporal variation of land use carbon income and expenditure and the coupling coordination degree in the Beibu Gulf urban agglomeration area in 2000, 2010, and 2020, the entropy weight method and TOPSIS method were combined to measure the carbon compensation closeness of 15 cities in 2020 in order to construct a comprehensive evaluation system of carbon compensation and to introduce a three-dimensional magic square unit model to initially construct carbon compensation levels for functional zoning research. [Results] ① From 2000 to 2020, the carbon balance of the Beibu Gulf urban agglomeration showed an overall increase, the main carbon emission area at the municipal scale showed a “core-periphery” structure, and the main absorption area has shown a “barb” spatial pattern. ② From 2000 to 2020, the carbon sources and sinks in the Beibu Gulf urban agglomeration area showed a northwest-southeast direction, except for the Guangxi region that showed a northeast-southwest dominant direction, with a stable spatial distribution center of gravity. ③ From 2000 to 2020, the coordinates of carbon sources and carbon sinks in the urban agglomeration area were greater than 0.5. Furthermore, the level of carbon emission and carbon absorption were high, showing relatively high coupling coordination. [Conclusion] There was obvious spatio-temporal heterogeneity in the carbon budget of the Beibu Gulf urban agglomeration, and the degree of coupling coordination between carbon emissions and carbon absorption were high. In order to further explore diversified paths to achieve the “double carbon” goal, regional resource capacity, carbon emission intensity, and economic development conditions should be considered in the future so that the inter-regional carbon compensation system of urban agglomeration areas can be improved.